PENGARUH PELATIHAN DAN PENEMPATAN TERHADAP KEPUASAN KERJA BAGIAN PRODUKSI PT. OERLIKON BALZERS ARTODA INDONESIA - Baeha Waruwu; Freddrick Tiagita P (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
The position of human resources as an organizational partner can be realized through the extent to which the company or organization is able to develop the capabilities and skills of all members in the organization or company. This study aims to analyze the partial and simultaneous influence of training and placement on job satisfaction of employees of PT. Oerlikon Balzers Artoda Indonesia. This study involved 42 respondents. The results showed that training and placement had a partial and simultaneous effect on employee job satisfaction.